Análisis de las capacidades dinámicas en las organizaciones, tendencias actuales y barreras al crecimiento en el TECNM/ITS – Fresnillo (Ágora UNLaR, 2025)
This article analyzes the development and evolution of dynamic capabilities, focusing on cur-rent trends in theirstudy and application within organizations. Dynamic capabilities have gained significant attention in recent yearsdue to their relationship with innovation, adaptation, and organizational resilience. However, organizations facebarriers to their effective implementation, such as resistance to change, lack of technological integration, andineffective knowledge management. Key trends include digitalization, technological transformation, andsustainability, which are reshaping how dynamic capabilities are developed. The article aims to provide acomprehensive overview of these capabilities, identifying emerging trends and persistent obstacles. It addressestwo main research questions: What are the current trends in the study of dynamic capabilities? And what barrierslimit their implementation in organizations? his approach highlights the im-portance of the topic, emphasizingtrends and framing the questions that guide the analysis.